Sistem Informasi Penjualan Online Berbasis Web Pada Toko Citra Parfum - Yunianto , Imam; Mutoffar , Muhamad Malik; Pratama , Syadam (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
This research aims to develop an online sales system (e-commerce) for Citra Parfum store in Tambun Selatan, Bekasi Regency. The store faces challenges in achieving sales targets and low customer numbers due to limited promotion through conventional channels and its hidden location within a residential area. The research utilizes the method of information system development, utilizing Visual Studio Code as a medium for creating the e-commerce website. The developed system includes the display of perfume products along with relevant information, a shopping cart, the checkout process, and online payment. This study proposes the implementation of a web-based e-commerce for Citra Parfum store. With the online sales system, it is expected that the number of sales transactions will increase, the marketing reach will expand, and buyers will be able to transact more easily. The research results are also expected to provide practical benefits to the management of Citra Parfum in improving customer satisfaction through the implementation of the online sales system.